Tendencies of Development of Foreign Investment in the World Market of Services of the Industrial Construction - E. N. Smirnov (Управление)
Basic and functional priorities of innovative development of our country should be estimated and considered, first of all, in the context of its cooperation with the European Union (EU) which is our main external economic partner. It is caused by a complex of historical, economic, geographical, cultural and political factors and regularities. However progressive approaches of developed countries to forming of the national innovative systems (NIS) are also important from the point of view of their use for the solution of the same problems in Russia. Forming of mechanisms of interstate regulation of innovative development at the level of the Eurasian Economic Union (EEU) shall consider: orientation to broad support of the basic and improving innovations, a combination of state regulation and a market mechanism in development of the innovative sphere, assistance to the international investment cooperation and a transfer of technologies, protection of interests of an innovative entrepreneurship, social aspects of orientation of interstate innovative policy. In the article the problems of development of an innovative cooperation at the level of EEU in the context of creation of effective integration consolidation are analyzed and generalized.